2013
DOI: 10.1021/am401933d
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Texture and Crystallinity of Evaporated Lead Phthalocyanine Thin Films for Near-Infrared Sensitive Solar Cells

Abstract: To achieve organic solar cells with a broadened spectral absorption, we aim to promote the growth of the near-infrared (NIR)-active polymorph of lead phthalocyanine (PbPc) on a relevant electrode for solar cell applications. We studied the effect of different substrate modification layers on PbPc thin film structure as a function of thickness and deposition rate (rdep). We characterized crystallinity and orientation by grazing incidence X-ray diffraction (GIXD) and in situ X-ray reflectivity (XRR) and correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 85 publications
1
60
1
Order By: Relevance
“…The molecular arrangements of polymorphs influence the optical and transport properties of thin films significantly. It has been demonstrated that the absorption spectrum of MPc is red shifted in the triclinic structure due to increased intermolecular interactions in this phase . In order to gain control over the organic thin films phase and morphology, organic molecular beam deposition has been effectively utilized to get good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular arrangements of polymorphs influence the optical and transport properties of thin films significantly. It has been demonstrated that the absorption spectrum of MPc is red shifted in the triclinic structure due to increased intermolecular interactions in this phase . In order to gain control over the organic thin films phase and morphology, organic molecular beam deposition has been effectively utilized to get good reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] As such both inorganic and organic thin fi lms have been employed as structural templating layers to improve device parameters. [5][6][7] Copper (I) iodide (CuI) has shown recent promise as an evaporable templating layer for small molecule photovoltaic applications.…”
Section: Doi: 101002/admi201400540mentioning
confidence: 99%
“…Shuttle cock-type phthalocyanines are groups of semi-conductive materials with Q-band absorption in red to near-infrared wavelength. Non planar phthalocyanine such as titanyl phthalocyanine (TiOPc), lead phthalocyanine (PbPc), and vanadyl phthalocyanine (VOPc) have a variety of crystal structure at phase transition between H-aggregation (phase I) and J-aggregation (phase II) that absorbs at longer wavelength [1][2][3]. They are applied for electronic and optical devices, chemical pigments and photovoltaic application as used for donor materials in organic solar cells [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%